Self-Regulated Learning Strategy Based on Problem Solving to Improve The Learners’ Learning Outcome - Santi Eka Ambaryani; Winarti Winarti (Jurnal Pembelajaran Fisika, 2021)
Self-regulated learning is an effort to manage an individual’s learning. This research aims to 1) determine the strategy of self-regulated learning (SRL) based on problem-solving toward the learners’ learning outcomes and 2) determine the learning outcome improvement of the learners in learning by using the SRL based-problem solving. This research is quantitative research with quasi-experimental type and pretest-posttest control group design. The sampling technique was purposive sampling. The research population covered all in Senior High School (SMA 5) Yogyakarta. The samples were from the tenth graders of Mathematics and Science Program 3 as the control group and Mathematics and Science Program 1 as the experimental group. The data collection methods consisted of test and non-test. The analysis result were, the hypothesis test showed that the applied strategy influenced the learners’ learning outcomes and the learners’ learning outcomes had improvements with the N-gain average score of 0.590, categorized moderate.Keywords: Problem-Solving, Self-Regulated Learning Strategy, Simple Harmonic MotionDOI: http://dx.doi.org/10.23960/jpf.v9.n1.202106